Apakah Aktualisasi Diri Berhubungan dengan Kebahagiaan?Suatu Kajian Filosofis-Psikologis - Anggairah, Marini Stannie (Asian Journal of Multidisciplinary Research, 2026)
This study explores the relationship between self-actualization and happiness within the framework of philosophical psychology. Self-actualization, as proposed by Abraham Maslow, represents the fulfillment of one's highest potential, while happiness is examined through both hedonic (pleasure-based) and eudaimonic (meaning-based) dimensions. The research employs a philosophical-psychological literature review, analyzing key works from influential thinkers like Maslow, Carl Rogers, Viktor Frankl, and Martin Seligman. By examining their contributions, the study investigates the conceptual foundations of self-actualization in humanistic psychology and its connection to happiness. The research also explores the ontological, epistemological, and axiological implications of these concepts, emphasizing the significance of understanding self-realization not just as a psychological process, but as an existential and moral journey. The findings suggest that while self-actualization contributes to deep, enduring happiness, it is essential to recognize the role of meaning and transcendence in achieving true fulfillment. This interdisciplinary approach offers valuable insights for understanding human well-being from both a philosophical and psychological perspective.